A feasibility study of ballet education using measurement and analysis on partial features of still scenes. (December 2016) - Park, So-Hyun; Hong, Gwang-Soo; Park, Sun-Woo; Nasridinov, Aziz; Park, In-Ja; Kim, Byung-Kyu; Park, Young-Ho
There have been a number of dance and ballet education systems using different multimedia devices. One of the well-known multimedia devices is Kinect which uses multiple built-in sensors. We focus on Kinect-based dance and ballet education systems. Existing systems that use Kinect cannot properly recognize the turnout movement. We propose the use of a lower body joint point estimation algorithm and a closest foot points estimation algorithm that can efficiently perform image localization for recognition of basic ballet movements. In addition, in order to evaluate correct ballet movements, we propose a method that extracts partial features from still scenes and performs measurements for knee and foot positions. The proposed method is the first ballet education system that properly measures movements of a ballet dancer.